(untitled) (Global Scientific Review, 2023)
The English language has been the common language of the world for decades. It is now impossible to find a country where learning English has not become a norm. While there are some people who would like to stick with their native language and who would prefer not to learn English, the benefits of learning and mastering English goes beyond the four corners of one’s own country. English is the most spoken language around the world. 1 out 5 persons understands it. It is estimated that there is are 400 million native speakers and 300 million that utilize English as a second language and an additional 100 million who use it as a foreign language. It is the language of science, of aviation, computers, diplomacy, and tourism. English is the official or co-official language from 45 countries and is spoken extensively in other countries where it does not have official position because is needed in many fields and jobs.